ANALYSIS OF THE CORRELATION BETWEEN SIGMA LEVELS AND REDUCTION OF ADDED VALUE IN WET EGG NOODLE PRODUCTS - Amelia Risky Camila; Teguh Soedarto; Ika Sari Tondang (International Journal of Multidisciplinary Research and Literature, 2023)
MSME Soponyono Noodle Mill is one of the MSMEs in Wonokusumo, Surabaya, that adds the value of wheat flour to wet egg noodle products. However, defects in its operation can cause the product to lose its added value. This study focuses on analyzing the relationship between sigma levels and decrease in added value in wet egg noodle products. The method used in this study is the calculation of level 6 sigma, the Hayami method, and simple linear regression. The results showed that the average defect value of Sigma noodles is 3,47, which states that the production process of wet egg noodles still has not reached the level of 6 Sigma. Wet egg noodle production has a high added value of Rp10.800/Kg with a ratio of 44%. The profit is Rp6.800 / Kg. The simple linear regression analysis results state the relationship (correlation) Sigma effect of 98,3% with a decrease in the added value of wet egg noodle products. This value is also evidenced by the Sig value of the sigma level variable is 0,001, more minor than alpha 0,05. As the sigma level approaches 6 (the highest quality level), the loss or reduction in its added value gets lower. This shows that efforts to increase the sigma level will positively impact the product’s added value